2010
DOI: 10.2135/cropsci2009.09.0535
|View full text |Cite
|
Sign up to set email alerts
|

Determining Salinity Threshold Level for Castor Bean Emergence and Stand Establishment

Abstract: Castor bean (Ricinus communis L.) is grown on marginal lands that can be prone to having medium to high salt concentrations. This study was done to identify a salinity threshold level for castor bean emergence and stand establishment. Seedlings were first cultured in organic matter–soil mixed media at different salinity levels (0.5, 3.6, 7.1, 10.4, and 13.6 dS m−1) and then transplanted into pots filled with soils at similar salinity levels (0.4, 3.6, 7.1, 10.4, and 13.6 dS m−1). Emergence, survival, seedling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…All the growth parameters including plant height, stem diameter, the weight of root, stem, leaf, and the whole plant and some physiological parameters including the activity of SOD and POD were even increased at the 50 mM salinity level as compared with the non‐salinity level, indicating that castor plants were not negatively affected at a low salinity level. This finding was partially in agreement with our previous study in which the salinity level of 3.6 dS m −1 significantly increased taproot length, average root length, the weight of root, stem, and the whole plant (Zhou et al, 2010). But different results were reported by Janmohammadi et al (2012), who found that 50 mM NaCl resulted in a significant decrease in the root weight and leaf of castor bean seedlings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All the growth parameters including plant height, stem diameter, the weight of root, stem, leaf, and the whole plant and some physiological parameters including the activity of SOD and POD were even increased at the 50 mM salinity level as compared with the non‐salinity level, indicating that castor plants were not negatively affected at a low salinity level. This finding was partially in agreement with our previous study in which the salinity level of 3.6 dS m −1 significantly increased taproot length, average root length, the weight of root, stem, and the whole plant (Zhou et al, 2010). But different results were reported by Janmohammadi et al (2012), who found that 50 mM NaCl resulted in a significant decrease in the root weight and leaf of castor bean seedlings.…”
Section: Discussionsupporting
confidence: 93%
“…Castor plant, as a salt‐tolerant crop, grows well in semiarid and arid regions, areas that often have low‐to‐medium saline concentrations (Jeschke and Pate, 1991, 1992). Its plantation has attracted the attention from both agronomists and producers (Zhou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of seed germination is usually expressed with parameters such as germination percentage, germination velocity, and germination vigor index. The vigorous growth of seedlings, often expressed with root and shoot growth, usually lays a solid foundation for an optimum plant population, especially under saline soil conditions (Zhou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The castor plant is tolerant to drought and adapted to many cropping conditions (BABITA et al, 2010;CARVALHO et al, 2010;ZHOU et al, 2010). In Brazil, new castor genotypes have been developed with a high yield potential, a short growing cycle, even maturation, indehiscent fruit, and a short stature and are suitable for mechanical harvesting techniques.…”
Section: Introductionmentioning
confidence: 99%